126 Impact of Elevating Feed Amounts in Late Gestation on Sow and Litter Performance. (7th May 2021) - Portal, Ximena A Paz; Rosero, David; Carter, Scott D
Abstract: The objective of this study was to investigate the effects of elevating feed amounts during late gestation on the performance of sows and their pigs during lactation. A total of 419 individually-housed sows were used. Sows were balanced by parity (P2 –P10) and body condition score (BCS, 1–5) on d 90 of gestation to 2 treatments [Control or bump-feeding (BP)]. Within each treatment, sows were fed a common gestation diet according to their body condition: (thin, BCS < 3 = 2.7 kg/day; ideal BCS 3 = 2 kg/day; fat, BCS > 3 = 1.6 kg/day). For sows allotted to BP, feed intake was increased by 0.91 kg/d on d 90. Data were analyzed for main effects of treatment and within body condition category. Bump-feeding decreased lactation ADFI of ideal sows (P = 0.015; 6.53 and 5.99 kg, for control and BP, respectively), but not of thin (P = 0.122, 6.05 and 6.80 kg) or fat sows (P = 0.136, 5.79 and 6.78 kg). The number of still-born pigs decreased when thin (P = 0.005, 1.63 and 0.93 pigs for control and bump-feeding) and fat sows (P = 0.133, 1.74 and 1.13 pigs) were BP. However, this was not observed for ideal sows (P = 0.779, 1.28 and 1.27 pigs). Moreover, piglet birth weight (measured in a subsample of 55 litters) improved with BP (P = 0.048; 1.36 vs 1.55 kg, for control and BP, respectively). The impact of BP on birth weight was more evident for fat sows (P = 0.08, 1.25 and 1.61 kg). This resulted in a greater proportion of small pigs (< 3.63 kg) at weaning in litters from fat sows that were not BP (P = 0.019; 7.41 vs 0%, for control and BP, respectively). In conclusion, elevating feed amounts in late gestation did not improve the performance of ideal sows but it positively impacted the performance of thin and fat lactating sows.